Deskripsi kemampuan berpikir kritis siswa dalam pemecahan masalah aritmetika sosial di SMPN 1 Labuhan Haji Tahun Ajaran 2020/2021 - Ayu Lestari Handayani; Nyoman Sridana; Junaidi Junaidi; Sri Subarinah (Griya Journal of Mathematics Education and Application, 2021)
The research aims to describe students' critical thinking ability in terms of social arithmetic problem problem 2020/2021. As for the indicators of critical thinking ability covering clarification, furtherment, strategy, and inference. This type of research is qualitative descriptive research with a quantitative approach. The method of data collection includes a test of the critical thinking ability of 3 items of description and interview. Based on data analysis, it could be concluded that: (1) the high category of subjects of 3 students, indicating that in the clarifying, subclassification, strategy, and inference parts can state the problem perfectly and completely (2) the only moderate number of subjects at 5 students, pointing out that in the clarifying, subclassification, strategy, and inference sections can present the problem less completely (3) next, the low number of subjects of 12 students, I will be able to explain that in the clarification,assement, strategy, and inference will be unable to declare the problem.